Cardiovascular safety of xanthine oxidase inhibitors: an optimistic and unfinished story - M. S. Eliseev; O. V. Zhelyabina (Современная ревматология, 2023)
Gout is associated with a high risk of cardiovascular diseases and associated mortality. Possible causes of the disease include persistent uncontrolled hyperuricemia, a chronic microcrystalline inflammation that develops in the vascular wall and even in atherosclerotic plaques. These processes, which contribute to oxidative stress and the formation of peroxidation products, may be a target for xanthine oxidase inhibitors — allopurinol and febuxostat. Their rational use, aimed at complete dissolution of urate crystal deposits in gout patients, results in improvement of endothelial function, lowering of blood pressure, and possibly reduction of all-cause and cardiovascular mortality. The effects on cardiovascular risk and safety of these drugs are believed to be comparable, greatly expanding the options for gout therapy.